Income implications of political capital and agricultural land use in western China - Komarek, Adam M.; Spoor, Max; Feng, Shuyi; Shi, Xiaoping (Emerald Publishing Limited, 2017)
The purpose of this paper is to explore the expansion of agricultural production into marginal lands, also known as “wasteland,” and examine the association between political capital, household income, and using additional marginal lands for agriculture in the Xinjiang Uyghur Autonomous Region of western China.The paper uses exploratory data analyses methods, including descriptive statistics, graphical analysis, econometrics and propensity score matching, and data from a 2008 survey of 342 households in Awat County of Aksu Prefecture to explore the role of political capital in an agricultural household setting.Preliminary results suggest that wasteland usage has a positive association with income, and that household political capital, in the form of Communist Party membership or being a village cadre, correlates with wasteland usage because it improves access to irrigation water.A constant topic of debate in China is the role of political capital in influencing livelihoods. The authors aim to add modest insights into this debate and provide a starting point to foster additional debates regarding the role of political capital, rural livelihoods, and natural resource usage.